2023
DOI: 10.1096/fj.202201582r
|View full text |Cite
|
Sign up to set email alerts
|

OASL knockdown inhibits the progression of stomach adenocarcinoma by regulating the mTORC1 signaling pathway

Abstract: The present study investigated the effects of 2′‐5′ oligoadenylate synthetase‐like (OASL) on the biological functions of stomach adenocarcinoma (STAD) cells and tumor formation in nude mice. The differential expression levels of OASL in the different cancer types from TCGA dataset were analyzed using gene expression profiling interactive analysis. Overall survival and the receiver operating characteristic were analyzed using the KM plotter and R, respectively. Furthermore, OASL expression and its effects on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…These enzymes influence the detection and response to viral infections ( Guo et al, 2012 ). It also regulates cell growth, proliferation, and apoptosis ( Zhao et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes influence the detection and response to viral infections ( Guo et al, 2012 ). It also regulates cell growth, proliferation, and apoptosis ( Zhao et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…As reported, OASL is closely related to viral infection response and autoimmune diseases 13 . In addition, OASL plays a role in a variety of tumors, such as breast cancer, lung cancer, bladder cancer, and gastric cancer 14–17 . It has been reported that OASL is overexpressed in PDAC and is associated with poor outcomes in patients 18 .…”
Section: Introductionmentioning
confidence: 93%
“…13 In addition, OASL plays a role in a variety of tumors, such as breast cancer, lung cancer, bladder cancer, and gastric cancer. [14][15][16][17] It has been reported that OASL is overexpressed in PDAC and is associated with poor outcomes in patients. 18 Furthermore, we found that Pi16 can promote PDAC cell proliferation by regulating OASL, suggesting that the Pi16/OASL axis may be a promising new target for PDAC diagnosis and treatment.…”
mentioning
confidence: 99%
“…Recurrence and tumour metastasis [34] Gastric cancer GES-1 and STAD cell lines Regulating mTORC signaling pathway Tumour progression [35] Oral cancer HEp-2…”
Section: Breast Cancer Bioinformaticsmentioning
confidence: 99%